Antimicrobial Strategies for Cystic Fibrosis - Møller, Rikke; Pressler, Tacjana; Qvist, Tavs (Seminars in Respiratory and Critical Care Medicine, 2022)
Lung infection is the leading cause of death in cystic fibrosis (CF), and antimicrobial therapies are the backbone of infection management. While many different strategies may be applied, rigorous microbiological surveillance, intensive eradication therapy, and long-term maintenance therapy based on inhaled antibiotics may be considered the main strategy for infection control in individuals with CF. While most of the existing evidence is based on infection with Pseudomonas aeruginosa, other important pathogens causing lung inflammation and deterioration exist and should be treated despite the evidence gap. In this chapter, we describe the approaches to the antimicrobial treatment of the most important pathogens in CF and the evidence behind.
Keywords: Pseudomonas aeruginosa; Staphylococcus aureus; nontuberculous mycobacteria; evidence; eradication; inhaled antibiotics